2019
DOI: 10.1097/hjh.0000000000001909
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and hypertension status in Afro-Caribbean men

Abstract: Objective: African ancestry individuals are at high risk for hypertensive cardiovascular disease (CVD) and could benefit from early detection of arterial stiffening. We tested the association between the 2017 ACC/AHA hypertension categorizations, which include new blood pressure (BP) cutoffs and a definition for elevated BP, and arterial stiffness in 772 Afro-Caribbean men aged 50+ years (mean 64 years). Methods: Arterial stiffness was assessed by brachial-ankle pulse-wave velocity (PWV) using a waveform analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…They found high CF-PWV was associated with a trend towards increasing cardiovascular risk in both non-hypertensives and hypertensives, a finding that may support the crucial importance of arteriosclerosis in both populations. The results of the present study showed that the higher level of arteriosclerosis was independently associated with uncontrolled hypertension, which was consistent with other studies in specific population, such as in men [4] and in patients with chronic kidney disease [5]. In the study, we also found independent associations between uncontrolled hypertension and male, TC, BMI, FPG, and creatinine in all models.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They found high CF-PWV was associated with a trend towards increasing cardiovascular risk in both non-hypertensives and hypertensives, a finding that may support the crucial importance of arteriosclerosis in both populations. The results of the present study showed that the higher level of arteriosclerosis was independently associated with uncontrolled hypertension, which was consistent with other studies in specific population, such as in men [4] and in patients with chronic kidney disease [5]. In the study, we also found independent associations between uncontrolled hypertension and male, TC, BMI, FPG, and creatinine in all models.…”
Section: Discussionsupporting
confidence: 93%
“…A large community-based study from China found that age-related increase in BP seemed to be largely mediated by age-related change in arterial stiffness status assessed by brachial ankle artery pulse wave velocity (ba-PWV), and baseline arterial stiffness was associated with subsequent BP, rather than the opposite direction [3]. Furthermore, previous studies found that patients with uncontrolled hypertension had significantly greater ba-PWV in men aged ≥65 years [4] and had a higher ba-PWV or carotid radial pulse wave velocity in patients with chronic kidney disease ( n = 82) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Aortic stiffness has been considered as a subclinical target organ damage with prognostic value in hypertensive patients. 3,4 A number of studies proposed that increased aortic stiffness is associated with persistent hypertension in some subjects. 5,6 This vicious circle between HTN, aortic stiffness/distensibility and heart failure would be continued without any intervention whereas, early detection and appropriate interventions can reduce these complications.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a recent study in African-Caribbean males aged ≥ 65 years showed that arterial stiffness, quantified by brachial-ankle pulse wave velocity, was markedly higher in PHT individuals than in NBP individuals but indistinguishable from patients with HT [21]. Our previous studies have shown that increases in PWV-ES assessed by ufPWV were consistently synchronized with age, even in a young population of 30-39 years old [18].…”
Section: Discussionmentioning
confidence: 70%